Penguatan Sumber Daya Manusia Halal Di Rest Area KM 72A Tol Purbaleunyi Arah Bandung - Rachmat Darmawan; Fajar Azhari Julian; Novianti Rachmayani; Abdul Rochim; Andri Mulyana; Muhammad Adzka; Abdul Haris Muchtar; Sujoko Winanto (SocietalServe: Journal of Community Engagement and Services, 2025)
Halal Product Processing (P3H) certification mentoring is a community service activity aimed at helping P3H training participants obtain halal certification in halal human resource competencies. The research was conducted by mentoring halal human resource participants around the KM 72A Rest Area. The method of this activity is PAR (Participatory Action Research) to be able to answer partner problems directly through a combination of knowledge transfer, field practice and ongoing coaching. Mentoring is carried out by training P3H participants by providing pre- and post-tests, as well as creating SiHalal accounts and of course uploading documents to the application. Conducting simulations in conducting halal verification and validation for assisted MSMEs. Training is carried out until P3H participants are eligible to receive certificates. The result of this service is the certification of P3H training participants, which is expected to provide added value for participants and the community around the KM 72A Rest Area and of course, public or buyer confidence in the sustainability of the halal zone at the KM 72A Rest Area